The influence of soil treatment and irrigation methods on tomato yield and quality in the lowlands of Dagestan - Kurbanov, S A; Magomedova, D S; Dzhambulatova, A Z (IOP conference series. Earth and environmental science, 2021)
A positive effect of irrigation of meadow-chestnut soil on soil fertility was described for the dry-steppe zone of Dagestan. The object of research was tomatoes (Gift variety) planted on irrigated lands of Dagestan. The subject of research is tillage and irrigation methods. The influence of agrotechnical methods on agrophysical soil properties, level and quality of tomatoes was determined. Maintaining the moisture of the active soil layer within 80...100 % NV can optimize agrophysical fertility indicators of the meadow-chestnut soil. In combination with tillage at a depth of 0.23...0.25 m, it ensures the tomato yield of 80...86 t/ha.